The Influence of Community Participation, Village Government Support, and Member Motivation on the Success of the Karang Taruna Program in Ngorean Village, Gantiwarno, Klaten - Dwi Kristanto; Maruji Pakpahan; Widi Wahyudi; Aris Wahyu Kuncoro (Jurnal Price : Ekonomi dan Akuntasi, 2026)
The success of Karang Taruna programs plays an important role in supporting rural development and community empowerment. Program success is influenced by several factors, including community participation, village government support, and member motivation. This study aims to examine the effects of community participation, village government support, and member motivation on the success of the Karang Taruna Program in Ngorean Village. A quantitative approach with a survey method was employed. The study population consisted of members of Karang Taruna in Ngorean Village, while the sample was selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS), including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The findings indicate that community participation, village government support, and member motivation have positive and significant effects on the success of the Karang Taruna Program, both individually and simultaneously. These findings suggest that strengthening community involvement, enhancing institutional support from village governments, and improving member motivation are essential for achieving sustainable and effective youth development programs. The study is expected to provide practical recommendations for village governments and Karang Taruna administrators in improving program implementation and strengthening community-based youth organizations.